Factors Influencing Maternal Mortality from Severe Preeclampsia and Eclampsia - Khusen, Denny (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To analyze risk factor, both clinical and laboratory findings, associated with maternal mortality from severe preeclampsia and eclampsia in Atma Jaya Hospital. Methods: This was a retrospective case control study. All medical records of maternal death associated with severe preeclampsia and eclampsia between 1st January 2009 and 31st December 2011 were obtained and then information about risk factors were collected and tabulated. Risk factor analyzed were maternal age, gestational age, parity, coexisting medical illness (hypertension), antenatal examination status, maternal complications, systolic and diastolic blood pressure at admission, and admission laboratory data. Results: There were 19 maternal deaths associated with severe preeclampsia and eclampsia during period of study (Consisted of 6 cases of eclampsia and 13 cases of severe preeclampsia). Maternal mortality rate for severe preeclampsia and eclampsia were 16.7% and 33.3% respectively. Multivariate analysis identified the following risk factors associated with maternal death: gestation age